STANDAR PELAYANAN PEMBUATAN E-KTP DI KANTOR KECAMATAN BATI-BATI (BERDASARKAN PERATURAN BUPATI NOMOR 29 TAHUN 2018) - Widiati Widiati (stiatabalong.ac.id, 2020)
The KTP-making service is one example of a form of public service provided by government officials. In this study, the aim of this research is to find out the service standards for making E-KTP at the Bati-Bati District Office, in terms of the aspects of service time, service fees / rates, facilities and infrastructure or service facilities, competence of service providers and number of service implementers. This study used a qualitative approach to descriptive research, and the data collection techniques used in this study were observation, interviews, questionnaires and documentation. Whereas for the analysis of the data used is using an Interactive Analysis Model. Based on the results of research and discussion, it shows that the standard of service for making E-KTP at the Bati-Bati District Office of Tanah Laut Regency is running well, with the final percentage value of research results of 80.6%. This result was obtained based on 5 aspects, namely the aspect of the service period was included in the good category as much as 67%, the cost / tariff aspect of the service was included in the very good category as much as 95%, the aspect of facilities and infrastructure or service facilities was in the good category as much as 77%, the aspect of competence service providers included in the good category as much as 78%, and aspects of the number of service providers included in the excellent category as much as 86%. With the overall results showing a good percentage, it is necessary to have consistency to continue to provide excellent service and improve the quality of service from all aspects in making E-KTP at the Bati-Bati District Office, Tanah Laut Regency. Keywords: Service Standards, e-KTP, Perbub